1996
DOI: 10.1139/y96-143
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and contractile responses of fast- and slow-twitch rat skeletal muscles to ischemia

Abstract: Complete occlusion of blood flow to rat hind limb by tourniquet was used to study the effects of total ischemia for 1, 2, and 3 h on contractile function and metabolic behaviour of two muscles composed predominantly of either fast-twitch (extensor digitorum longus, EDL) or slow-twitch (soleus, SOL) fibres. Percent loss in twitch force (Pt) was greater (p < 0.05) in SOL than EDL during the first 45 min of ischemia. Following 1 h of ischemia, ATP concentration was lower (p < 0.05) than in the contralateral contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
1

Year Published

2001
2001
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 12 publications
0
3
1
Order By: Relevance
“…This result is different from previous studies in that 1-h of tourniquet ischemia significantly reduced glycogen levels (Carvalho et al, 1996;Fraser et al, 1998). It could be due to the treatment protocol utilized, allowing a 30-min recovery following ischemia, which elicited a rapid hypoxia-induced increase in glucose transport.…”
Section: Discussioncontrasting
confidence: 95%
See 1 more Smart Citation
“…This result is different from previous studies in that 1-h of tourniquet ischemia significantly reduced glycogen levels (Carvalho et al, 1996;Fraser et al, 1998). It could be due to the treatment protocol utilized, allowing a 30-min recovery following ischemia, which elicited a rapid hypoxia-induced increase in glucose transport.…”
Section: Discussioncontrasting
confidence: 95%
“…This is demonstrated by the fact that ischemia significantly decreases muscle glycogen levels (Purshottam et al, 1977;Fraser et al, 1998;Carvalho et al, 1996;Katz, 1988); and treatments that enhances carbohydrate metabolism protects muscles from severe ischemic damage (Lopaschuk, 2000;Keller et al, 1998). GLUT4 protein, the main glucose transporter expressed in skeletal muscle (Olson and Pessin, 1996), is found to play a key role in the regulation of muscle glycogen storage (Ren et al, 1993;Hansen et al, 1995;Tsao et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Dietz suggested that high threshold motor units rather than low threshold units are inhibited during acute ischemia. Nevertheless, studies on rat muscles have shown a greater decline in twitch force in slow muscle than in fast muscle during the first 45 minutes of ischemia, particularly during the first 15‐30 minutes . Likewise, Gossen et al reported markedly greater declines in twitch force in slow contracting motor units than in fast units during very low‐force (~5%‐10% of MVC) voluntary ischemic contractions in human subjects.…”
Section: Fatigue and Recovery In The Muscle Fibre Types With Ischemicmentioning
confidence: 99%
“…The free radical NO is a messenger molecule involved in various biological functions (1012). NO is synthesized by a complex family of nitric oxide synthase (NOS) enzymes (13).…”
Section: Nitric Oxide In Chronic Tension-type Headachementioning
confidence: 99%